Efficacy of the Combined Use of Bed Sill and Sacrificial Piles to Control Local Scour around Circular Bridge Piers - Vahid Javidi Vahdati; Ahmad Ahmadi; Amirabbas Abedini; Manouchehr Heidarpour (Shock and Vibration)
In this study, the results are presented and discussed from laboratory test campaigns specifically designed to investigate the behavior of sacrificial piles as a countermeasure against local scouring at a circular bridge pier and clear-water conditions with flow intensity slightly below the threshold of sediment motion. Sacrificial piles are assessed on the upstream side of the pier in two transverse and triangular arrangements. Piles can reduce scouring by deflecting the flow and creating a low-velocity wake region behind them. The efficiency of the piles against local scouring depends on the diameter of the piles, the number of piles, and the angle of the wedge. The investigation was aimed at evaluating the effectiveness of the sacrificial piles as a function of different dimensionless groups. It was found that the triangular arrangement of sacrificial piles has better results than the transverse arrangement. The results showed that the triangular sacrificial piles reduced the maximum local scour depth at the pier to 37.2% in the best configuration. Combined countermeasures were tested, which were composed of sacrificial piles and a bed sill downstream of the pier; in the best configuration, the scour depth reduction in front of the pier reached 51.1%. The increased efficiency of the combination of bed sill and sacrificial piles (BSSP) is an advantage that can reduce the risk of pier failure when the duration of the flood is short. This last result shows that a combination of BSSP may be a very effective countermeasure against local scouring at bridge piers. Finally, the coherent turbulent flow structure around the best combination of BSSP was investigated, and its effect on the bed scouring pattern was studied. A 3D analysis of the bursting process was used. Turbulence characteristics, as well as the occurrence and transition probabilities of bursting events, were calculated. The obtained results confirmed the quite effective effect of the combination of these two countermeasures in reducing the scour depth.